الکفاءات المهنیة للنشر الالکترونى :انعکاس للواقع فى العالم العربى - د. خالد عبد الفتاح محمد; د. منى فاروق على (المجلة الدولية لعلوم المكتبات والمعلومات)
The publishing industry has dramatically changed in the last twodecades. Turning towards electronic publishing, (EP) has required crucialdevelopments, one of which is to equip specialists with a variety of competenciesfor performing the technical and managerial tasks of (EP). To date, no study hascomprehensively investigated the requisite competencies for these tasks and thesources of learning and qualifying EP professional, especially in Egypt and theArab World. This paper identifies professional competencies for each taskthrough a proposed matrix. To design this matrix, several related studies havebeen consulted to collect the defined competencies. Afterwards, a survey hasbeen designed and distributed to explore the application of these competenciesin the real EP practices. Finally, a Focus Group has been designed to assign therequired competencies for each surveyed task. The results showed that the mostpracticed tasks are: EP planning, and acquisition. On the other hand, and in orderto acquire knowledge and experience, specialists often rely on directcommunication with experts and their colleagues at work and also designprofessional training courses. User support and communication are the mostrequired competencies for (EP) tasks. Further, disciplinary knowledge categoryrepresents the highest weighted category among three categories ofcompetencies. The matrix could be applied as a competence-based professionalformal education and job training framework, which would help students andtrainees meet the fundamental requirements of the labor market.